The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.molstruc.2021.131394
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and dynamics studies of Nicotinamide Riboside as a potential multi-target nutraceutical against SARS-CoV-2 entry, replication, and transcription: A new insight

Abstract: The highly contagious Coronavirus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which is a newborn infectious member of the dangerous beta-coronaviruses (β-CoVs) following SARS and MERS‐CoVs, can be regarded as the most significant issue afflicting the whole world shortly after December 2019. Considering CoVs as RNA viruses with a single-stranded RNA genome (+ssRNA), the critical viral enzyme RNA dependent RNA polymerase (RdRp) is a promising therapeutic target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The administration of NMN and NR to rodents, Caenorhabditis elegans (nematodes), and Drosophila melanogaster (fruit flies) has been shown to prolong lifespan and alleviate age-related physiological decline 38 40 . In other reports, NMN and NR have been suggested to bind to ACE2 and IMPDH, along with SARS-CoV-2 viral proteins (Spro, Mpro, PLpro, RdRp) by molecular docking and dynamics simulations, suggesting a potential therapeutic effect of NMN and NR in the treatment of COVID-19 41 .…”
Section: Introductionmentioning
confidence: 84%
“…The administration of NMN and NR to rodents, Caenorhabditis elegans (nematodes), and Drosophila melanogaster (fruit flies) has been shown to prolong lifespan and alleviate age-related physiological decline 38 40 . In other reports, NMN and NR have been suggested to bind to ACE2 and IMPDH, along with SARS-CoV-2 viral proteins (Spro, Mpro, PLpro, RdRp) by molecular docking and dynamics simulations, suggesting a potential therapeutic effect of NMN and NR in the treatment of COVID-19 41 .…”
Section: Introductionmentioning
confidence: 84%
“…The recent Omicron variant is characterized by 32 mutations in the spike glycoprotein, including 15 of them in the RBD [ 55 ]. Numerous molecular modeling docking studies on natural compounds have been carried out to evaluate their anti-ACE2 activity by the preventing RBD–ACE2 interaction [ 56 , 57 , 58 ]. Laboratory and clinical data support the possible advantages that some bacterial and molecular compounds may determine in the immune response to respiratory viruses and their regulatory role in systemic inflammation or endothelial damage, both representing two essential aspects of COVID-19 [ 59 ].…”
Section: Nutraceuticals and Dietary Supplements Against Covid-19 Dise...mentioning
confidence: 99%
“…Nicotinamide analogs, such as nicotinamide riboside (NR) and nicotinamide mononucleotide (NMN), are an important class of natural vitamin derivatives. A relevant study found that it can effectively inhibit ACE2, so it is considered a potential inhibitor for the treatment of COVID-19 ( 113 ). However, these are only theoretical speculations and almost no basic or clinical research verification.…”
Section: Potential Therapeutic Strategies and Promising Anti-sars-cov...mentioning
confidence: 99%